PENDOKUMENTASIAN SARANA DAN PRASARANA PADA RUMAH DUKA (STUDI PADA YDSP DAN BUMI BARU II): Documentation of Facilities and Infrastructure in Funeral Homes (Study Case: YDSP and Bumi Baru II) - Stevanny Priska Suwanto Putri; Irena V.G Fajarto; Yunita Setyoningrum (Jurnal Dimensi Seni Rupa dan Desain, 2023)
A funeral home is a space where people can carry out the last rite of honor for the dead. In Indonesia, specifically for some religions or beliefs adopted by each family has a tradition where the burial is done in a funeral home with a procession of worship carried out to escort the deceased. These processes have their facilities and infrastructure. In the aspect of infrastructure, all activities that take place are located and carried out in each different room, and the aspect of facilities is the equipment used to carry out each activity in the burial process. In general, there are no specific standards that describe the standard facilities and infrastructure that must be owned by a funeral home. Therefore, the purpose of this research is to document the existing facilities and infrastructure in a funeral home so that in the future it can assist in studies relating to a funeral home. The method used in this study is the study of literature, field observations to two funeral homes, and interviews with funeral home management. The main results of this research are inventory list of the needs that are the optimal needs of the two funeral homes through the data obtained. It is hoped that the results of this study can become guidelines for further research relating to existing facilities and infrastructure at the funeral home. Keywords: equipment, burial, corpse, funeral home